1979
DOI: 10.1111/j.1365-2621.1979.tb09113.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of Proteolytic Enzymes on Bovine Myofibrils

Abstract: The effect of cathepsin D from muscle and spleen on bovine myofibrils has been examined under postmortem pH conditions using sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis, scanning electron microscopy (SEM) and electron spin resonance spectroscopy (ESR). Cathepsin D causes a degradaticy of 2 disks of the myofibrils and has a relatively selective action on the myofibrillar proteins in comparison to the plant derived enzyme papain. The heavy chain of myosin (200,000 daltons) was degraded to fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The degradation of myosin heavy chain as a result of the action of cathepsin D produced two major groups of fragments with molecular weights of approximately 120,000 and 90,000. The latter fragments are of sufficient size to be myosin S-1 fragments as proposed in several investigations (Robbins et al 1979;Yates et al 1983;Elgasim et al 1985). It would be of interest to know which regions of the myosin molecule were attacked by cathepsin D and how the enzyme might participate in disassembly of the thick filament but these questions will have to be addressed in future research.…”
Section: Discussionmentioning
confidence: 66%
“…The degradation of myosin heavy chain as a result of the action of cathepsin D produced two major groups of fragments with molecular weights of approximately 120,000 and 90,000. The latter fragments are of sufficient size to be myosin S-1 fragments as proposed in several investigations (Robbins et al 1979;Yates et al 1983;Elgasim et al 1985). It would be of interest to know which regions of the myosin molecule were attacked by cathepsin D and how the enzyme might participate in disassembly of the thick filament but these questions will have to be addressed in future research.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, among the known proteolytic enzymes, CAF is unique in its inability to degrade myosin (Table 3). Together, these basic experimental findings inculpate CAF as the agent responsible for most postmortem proteolysis of myofibrillar proteins, even though cathepsins L (Matsukura et al 1981) and D both can produce 3OKdalton polypeptide fragments when incubated with troponin or myofibrils, and cathepsin D can degrade Z-disks in myofibrils at pH 5.2 to 5.3 (Robbins et al 1979).…”
Section: Which Proteolytic Enzymes Cause Tenderizationmentioning
confidence: 93%
“…These collagens were shown to be resistant to the action of papain, trypsin, and chymo trypsin. Robbins et al (1979) used SDS (sodium dodecyl sulphate) gel electrophoresis to show the effect of papain on bovine myofibrils.…”
Section: Enzyme Actionmentioning
confidence: 99%
“…Actomyosin was less rapidly digested than the myosin. Robbins et al (1979) showed that cathepsin-D extracted from muscle or spleen degraded myofibrils under postmortem pH conditions (5.1-5.3)…”
Section: Sds Electrophoresis Of the Myofibrillar Proteins Indicatedmentioning
confidence: 99%
See 1 more Smart Citation